2016
DOI: 10.1186/s12883-016-0690-4
|View full text |Cite
|
Sign up to set email alerts
|

Ethiopian teachers: their knowledge, attitude and practice towards epilepsy

Abstract: BackgroundIn Ethiopia where the burden of epilepsy is highest among school age children and teenagers, and where people with epilepsy (PWE) and their relatives suffers from high level of perceived stigma, there had not been any study that assessed the knowledge, attitude and practice of teachers towards PWE. This study aims to assess and understand the social and demographic determinants of knowledge, attitude and practice of teachers towards PLW in Addis Ababa, Ethiopia.MethodsMultistage cluster sampling proc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
34
3
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(52 citation statements)
references
References 14 publications
(27 reference statements)
6
34
3
6
Order By: Relevance
“…Epilepsy is considered to be a psychiatric illness by 15.9% of teachers surveyed in our study. This percentage is higher than the percentages observed among South Korean teachers (3.5%) and Egyptian teachers (10.2%) and lower than that observed among Ethiopian teachers (25.9%) (Gebrewold et al, 2016;Lee et al, 2010;Shehata & Mahran, 2010). These differences could be explained by several parameters such as the socio-cultural context, the religious beliefs of the population, and the education system.…”
Section: Discussioncontrasting
confidence: 63%
See 1 more Smart Citation
“…Epilepsy is considered to be a psychiatric illness by 15.9% of teachers surveyed in our study. This percentage is higher than the percentages observed among South Korean teachers (3.5%) and Egyptian teachers (10.2%) and lower than that observed among Ethiopian teachers (25.9%) (Gebrewold et al, 2016;Lee et al, 2010;Shehata & Mahran, 2010). These differences could be explained by several parameters such as the socio-cultural context, the religious beliefs of the population, and the education system.…”
Section: Discussioncontrasting
confidence: 63%
“…In this study, the main transmission routes reported were the contact with the places of crisis, physical contact with an epileptic person, and contact with saliva. On the other hand, low proportions ranging from 1% to 11.9% of teachers considering epilepsy as a contagious disease have been reported in other African studies (Gebrewold, Enquselassie, Teklehaimanot, & Gugssa, 2016;Millogo & Siranyan, 2004;Shehata & Mahran, 2010). In some Asian studies, epilepsy is considered to be contagious in 0.2-15.3% of teachers surveyed and in 44.4-83.6% as a brain disease (Alkhamra, Tannous, Hadidi, & Alkhateeb, 2012;Lee, Lee, Chung, Yun, & Choi-Kwon, 2010;Thacker, Verma, Ji, Thacker, & Mishra, 2008).…”
Section: Discussionmentioning
confidence: 91%
“…7 Our cohort of 235 patients had a broad age distribution, ranging from 1-to 78-years-old, with a substantial proportion younger than 20 years: up to 42% of the children included in our study were younger than10 years old and 24% were even younger than 2 years. [17][18][19] Several findings point to stigmatization of PwE. Indeed, limited information is available on the etiology and exact diagnosis of seizure type or syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…It is unclear whether this is due to stigma or cognitive decline in our patients. [17][18][19] Several findings point to stigmatization of PwE. Sebera et al 20 reported in 2005 that more than two-thirds of the Rwandan population considered PwE not apt to get married.…”
Section: Discussionmentioning
confidence: 99%
“…However, when analyzing studies published at national and international levels, no consensus in the literature has yet been observed regarding the influence of educational levels on beliefs and attitudes towards epilepsy, thus showing the lack of information regarding the disease affects all educational levels and may be a factor of considerable influence on inappropriate knowledge. Some research shows that inadequate knowledge is more closely associated with lower levels of education, while other studies conducted with people with higher education also show the remarkable presence of inappropriate beliefs [2,5,18,19,20,21].…”
Section: Discussionmentioning
confidence: 99%